2011
DOI: 10.1111/j.1365-2613.2010.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance plus hyperlipidaemia induced by diet promotes retina microaneurysms in New Zealand rabbits

Abstract: The animals with diet-induced impaired glucose tolerance combined with hypercholesterolaemia gained weight, increased blood glucose, total cholesterol, LDL-C and triglycerides and decreased HDL-C (P < 0.05 vs. baseline). Fructosamine levels and the homeostasis model assessment of insulin resistance (HOMA-IR) index were increased, while there was a reduction in the HOMA-β (P < 0.05 for all vs. baseline). Histomorphologic findings of this model were aortic atherosclerosis, hepatic steatofibrosis and glomerular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…It was realized several decades ago that high intake of saturated fat in the diet significantly enhanced the development of the atherosclerotic and autoimmune lesions in aorta of the autoimmune-prone B/W mice, which were known to develop severe glomerulonephritis and vasculitis (12). Numerous studies thereafter demonstrated that HFD impaired the structure and function and increased the lesion in different vascular beds (18,31,37,42). Recent studies that focused on the cerebral vasculature have found that the dilator response to ACh was impaired in cerebral arterioles of HFD-fed apoEϪ/Ϫ mice (24) or in basilar artery of HFD-fed peroxisome proliferator-activated receptor (PPAR)-␥ knockdown mice (2).…”
Section: Discussionmentioning
confidence: 99%
“…It was realized several decades ago that high intake of saturated fat in the diet significantly enhanced the development of the atherosclerotic and autoimmune lesions in aorta of the autoimmune-prone B/W mice, which were known to develop severe glomerulonephritis and vasculitis (12). Numerous studies thereafter demonstrated that HFD impaired the structure and function and increased the lesion in different vascular beds (18,31,37,42). Recent studies that focused on the cerebral vasculature have found that the dilator response to ACh was impaired in cerebral arterioles of HFD-fed apoEϪ/Ϫ mice (24) or in basilar artery of HFD-fed peroxisome proliferator-activated receptor (PPAR)-␥ knockdown mice (2).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity was calculated by the homeostasis model assessment for insulin resistance (HOMA-IR) using the following equation: [insulin (mU/l) × (glucose (mg/dl)/18)]/22.5 (Helfenstein et al, 2011). Low HOMA-IR values indicate high insulin sensitivity, whereas high HOMA-IR values indicate low insulin sensitivity (insulin resistance).…”
Section: Evaluation Of Insulin Sensitivitymentioning
confidence: 99%
“…Several high-sugar diet models have been developed including mice, rats, rabbits, dogs, and zebrafish [33,43,44,60,[78][79][80][81][82][83] that were persistently exposed to galactose developing retinopathy similar to that observed in human diabetes. Maintenance of galactose exposure results in continued disease progression.…”
Section: High-sugar Dietsmentioning
confidence: 99%
“…Rabbits fed a highsucrose diet for 24 weeks develop hyperfluorescent dots and microaneurysms appeared by the 12th week of the diet [27,81]. Dogs fed a diet with 30% increased galactose develop a more complex disease phenotype including DR and cataracts within 1 year; pericyte ghosts, microaneurysms, dot and blot hemorrhages, and acellular capillaries by 32 months; and basement membrane thickening by 60 months [43].…”
Section: High-sugar Dietsmentioning
confidence: 99%